The association between kidney function and major bleeding in older adults with atrial fibrillation starting warfarin treatment: population based observational study. (3rd February 2015) - Jun, Min; James, Matthew T; Manns, Braden J; Quinn, Robert R; Ravani, Pietro; Tonelli, Marcello; Perkovic, Vlado; Winkelmayer, Wolfgang C; Ma, Zhihai; Hemmelgarn, Brenda R
Abstract : Objective To determine rates of major bleeding by level of kidney function for older adults with atrial fibrillation starting warfarin. Design Retrospective cohort study. Setting Community based, using province wide laboratory and administrative data in Alberta, Canada. Participants 12 403 adults aged 66 years or more, with atrial fibrillation who started warfarin treatment between 1 May 2003 and 31 March 2010 and had a measure of kidney function at baseline. Kidney function was estimated using the Chronic Kidney Disease Epidemiology Collaboration equation and participants were categorised based on estimated glomerular filtration rate (eGFR): ≥90, 60-89, 45-59, 30-44, 15-29, <15 mL/min/1.73m 2 . We excluded participants with end stage renal disease (dialysis or renal transplant) at baseline. Main outcome measures Admission to hospital or visit to an emergency department for major bleeding (intracranial, upper and lower gastrointestinal, or other). Results Of 12 403 participants, 45% had an eGFR <60 mL/min/1.73m 2 . Overall, 1443 (11.6%) experienced a major bleeding episode over a median follow-up of 2.1 (interquartile range: 1.0-3.8) years. During the first 30 days of warfarin treatment, unadjusted and adjusted rates of major bleeding were higher at lower eGFR (P for trend <0.001 and 0.001, respectively). Adjusted bleeding rates per 100 person years were 63.4 (95% confidence interval 24.9 to 161.6) in participants with eGFR <15 mL/min/1.73m 2 compared with 6.1 (1.9 to 19.4) among those with eGFR >90 mL/min/1.73m 2 (adjusted incidence rate ratio 10.3, 95% confidence interval 2.3 to 45.5). Similar associations were observed at more than 30 days after starting warfarin, although the magnitude of the increase in rates across eGFR categories was attenuated. Across all eGFR categories, adjusted rates of major bleeding were consistently higher during the first 30 days of warfarin treatment compared with the remainder of follow-up. Increases in major bleeding rates were largely due to gastrointestinal bleeding (3.5-fold greater in eGFR <15 mL/min/1.73m 2 compared with ≥90 mL/min/1.73m 2 ). Intracranial bleeding was not increased with worsening kidney function. Conclusions Reduced kidney function was associated with an increased risk of major bleeding among older adults with atrial fibrillation starting warfarin; excess risks from reduced eGFR were most pronounced during the first 30 days of treatment. Our results support the need for careful consideration of the bleeding risk relative to kidney function when assessing the risk-benefit ratio of warfarin treatment in people with chronic kidney disease and atrial fibrillation, particularly in the first 30 days of treatment.